Cyclization mechanism and kinetics of poly(acrylonitrile-co-2-acrylamido-2-methylpropane sulfonic acid) copolymer investigated by FTIR spectroscopy - Zhipeng He (Elsevier, 2021)
Cyclization reaction of poly(acrylonitrile-co-2-acrylamido-2-methylpropane sulfonic acid) [P(AN-co-AMPS)] copolymer during thermal oxidative stabilization (TOS) process was investigated by FTIR and two dimensional (2D) correlation analysis technique. The results showed the mechanism of cyclization reaction at different temperatures were varying. At 200 °C, the cyclization reactions generated by autocatalytic cyclization mechanism. While at higher temperatures, the cyclization reactions took place through ionic cyclization mechanism and free radical cyclization mechanism. The AMPS comonomer could reduce the heat release of cyclization reactions and improve the stability at 200 and 230 °C. At higher temperatures, the cyclization reactions were facilitated rapidly. However, the oxidation and degradation reactions were also intense, which will cause the molecular chain to break and defects in the final carbon fibers (CFs). This research has theoretical guiding significance for the optimization of heat treatment conditions for PAN copolymers used as CFs.